THE RESULTS OF JOINT RUSSIAN - VIETNAMESE EXPEDITION IN THE ECONOMIC ZONE OF VIETNAM SEA ON THE R/V “AKADEMIC OPARIN”, 5-6/2007 - Hieu, Trinh The; Ben, Hoang Xuan; Ky, Pham Xuan; Hanh, Nguyen Kim; Dung, Nguyen Tien (Vietnam Journal of Marine Science and Technology, 2007)
Joint Russian - Vietnamese expedition aboard the research vessel “Akademic Oparin” organized by the Pacific Institute of Bioorganic Chemistry (PIBOC) and the Institute of Marine Biology (IBM) of the Far  East Branch of the Russian Akademy of Sciences (FEBRAS) together with the Institute of Oceanography (IO) of the VAST, Vietnam, from 05/5 to 08/6/2007 in the Economic zone of Vietnam sea. A main goal of the expedition is investigation of Biochemical and Biological diversity of main invertebrates, algae and microorganisms of a shelf of Vietnam and coral reefs of the Bien Dong. - The primary results of the investigation allowed us to access the status of coral reefs in the coastal and open waters of Vietnam. The reefs in the coastal waters have tended to be degraded severely due to the over-exploitations of resources by the exterminating methods. - During the expedition, we collected plenties of the precious specimens which are usefull for scientific  study and Oceanographic meseum. Among them, several samples are found at the first time in the deep sea,  such as white sphere sponge, pieces of gabro stone, red coral, and other veterbrates living in the bottom. - Total of samples collected during the investigation: Geological samples: 35 Biochemical samples: 39 Microbiological samples: 51 samples (263 strains) Soft coral samples: about 150 Specimens for Oceanographic meseum: about 200